The effect of body fluid balance on cycling peak power - Maciejczyk, M.; Szymanik, W. (Science & Sports, 2014)
Objective: Dehydration impairs aerobic performance but the influence of dehydration and rehydration on cycling peak power is contradictory. The purpose of the study was to evaluate both the influence of body dehydration and the influence of rehydration on the level of cycling peak power. Methods: Cycling peak power (CPP) was measured 3 times in 12 healthy males: in baseline testing, next after dehydrating the body using passive heat exposure (sauna), and after the sauna, with simultaneous hydration (in random order). Results: The level of total work, CPP and time to attain peak power were comparable with the dehydration (1.9% of body mass) during and after the sauna combined with the systematic replenishment of isotonic drinks, and was significantly (P < 0.05) higher (with the exception of the time to attain cycling peak power) in relation to the initial measurement. The absolute CPP increased about 20 W on average after dehydration, and 25 W on average after the sauna with rehydration. The relative cycling peak power significantly increased after dehydration (11.6 ± 0.6 W/kg) and after passive heat exposure with rehydration (11.6 ± 0.7 W/kg) in comparison to the initial level (11.2 ± 0.4 W/kg). Conclusion: The present results suggest that CPP was not affected by body fluid balance alterations. The research results show that moderate dehydration does not impair cycling peak power.